CHRIST IMAGE PROJECTION: ESTHETICS IN CHRISTIAN THEOLOGY - I Gde Jayakumara (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2015)
Through the controvertiality of The Last Temptation of The Christ we can learn, there is an intrinsic connection between theological aesthetic and moral theology: the theology of Christian praxis. In order to liberate, truth must capture the mind, goodness must enrapture the heart. The good and the true must appear as good and true for us. That is, truth must show its persuasiveness, goodness must show its attractiveness. The true and the good must be revealed as corresponding with our deepest human purposes and desires; in short, they must be apprehended as beautiful. Beauty can then be the instrument of conversion.